The Extent of Internet Auction Markets - Laurens de Haan; Casper de Vries; Chen Zhou (Tinbergen Institute, 2008)
Internet auctions attract numerous agents, but only a few become active bidders. A major difficulty in the structural analysis of internet auctions is that the number of potential bidders is unknown. Under the independent private value paradigm (IPVP)the valuations of the active bidders form a specific record sequence. This record sequence implies that if the number n of potential bidders is large, the number of active bidders is approximately 2 log n, explaining the relative inactivity. Empirical evidence for the 2 log n rule is provided. This evidence can also be interpreted as a weak test of the IPVP.
Keywords: D44; 330; bids as records; number of active bidders; Auktion; Internet; Auktionstheorie